Genetic Retrospect of Seedcotton Yield and its Components from a 6-Parent Gossypium hirsutum Diallel Cross Under Water Stress Conditions - Munaiza Baloch,; Muhammad Ibrahim Keerio,; Bashir Ahmad Ansari,; Moula Bux Kumbhar , (Journal of Basic & Applied Sciences, 2021)
A six-by-six complete F1 Gossypium hirsutum, L. diallel cross of three pre-screened drought tolerant and three drought susceptible varieties (CRIS-134, CRIS-342, SINDH-1, NIAB-78, SADORI and BH-160) was evaluated for genetic parameters during 2009 at Sindh Agriculture University farm, Tandojam. The characters studied were number of bolls per plant, sympodial branches per plant, seedcotton yield per plant and lintcotton yield per plant. The objective of such study was to assess the effect of irrigation stress on the genetic inheritance pattern of above quantitative traits as to how far the genetic parameters are affected due to irrigation stress in the F1 diallel generation. Irrigation treatments were four; normal seven irrigations schedule, five irrigations, four irrigations (medium stress) and three irrigations up to 150 days of crop maturity (stress conditions). CRIS-134 in seven, Sadori in five and CRIS-342 in four and three irrigations treatments were the most recessive parents contributing increasing boll number into their progenies while BH-160 in seven, CRIS-342 in five and Sindh-1 in four and three irrigations treatments proved to be the most dominant parents responsible for contributing decreased boll number per plant into their progenies. Seedcotton per plant was partial dominant in seven irrigations treatment while it inherited as an overdominant trait in five, four and three irrigations respectively. BH-160 was the most recessive of all with increased sympodia contributing attributes in seven and four irrigations whereas Niab-78 in five and CRIS-342 in stress were the most recessive parents. Sindh-1 was the most dominant parent in seven, five and three irrigation treatments while CRIS-342 in four irrigations yielded decreased sympodia contributing attributes into their progenies. Sindh-1 in seven, BH-160 in five and three and CRIS-342 in four irrigations treatments proved to be the most recessive parents with increasing seedcotton yield attributes while CRIS-342 in seven and five and Sindh-1 in four and three irrigations were the most dominant parents contributing decreased seedcotton yield into their progenies. Inheritance trend of lintcotton per plant was similar to that of seedcotton yield per plant.